新加坡公共空间的介入 ：戏剧盒社区剧场（2008-2017）的空间运用策略 = Intervening Singapore’s public spaces : spatial strategies of drama box’s community theatre (2008-2017) - 张棋汶 Teo, Qi Wen (2018)
“公共空间”的概念在新加坡涉及社会秩序和国家发展等问题，在官方话语中被赋予政治意识形态。由政府主导的空间规划和管理过程使公共空间成为国家展现霸权意识的场域。一般民众在日常生活的空间处于边缘位置，促使本地华语戏剧团体戏剧盒通过剧场形式介入公共空间，在非传统剧场空间推展社区剧场工作。本论文将研究戏剧盒社区剧场从 2008-2017 年的空间运用策略，探讨戏剧盒如何介入新加坡公共空间，改变“公共空间”在本地社会的既有空间意涵。戏剧盒通过具有社会行动主义精神的社区剧场，赋予民众重新塑造公共空间的权力，平衡民众与国家之间的权力架构，具有充权社群的意义。 The concept of a “Public Space” in Singapore is closely linked to the nation’s development and social order. As such, public spaces are heavily influenced by the state’s discourse and generally tend to be constructed with political ideologies in mind. As the planning and management of Singapore’s public spaces are generally state-led, public spaces are often regarded as sites representing the state’s hegemonic control over society and its citizens. The local community is often marginalised in the creation of these everyday lived spaces, motivating local Chinese theatre company, Drama Box, to intervene by staging community theatrical productions at non-conventional theatre venues in public spaces within Singapore. This paper aims to study the spatial strategies adopted by Drama Box’s Community Theatre from 2008-2017 in intervening Singapore’s public spaces. The staging of community theatre in everyday lived spaces has redefined the concept and meaning of “Public Space” within the local context. These community theatrical productions can also be understood as a form of social activism which empowers the local community to re-construct public spaces and counterbalances the power of the state.